The role of Northern European countries in the emergence of new training methodologies in distance running: a historical overview - Kelemen, B.; Benczenleitner, O.; Toth, L. (European Conference for the Sociology of Sport 2023, 2023)
This study aims to present the major training theoretical innovations in the history of modern distance running that can be traced back to the countries of Northern Europe and the possible underlying socio-historical reasons for them. Results: Since the beginning of modern sport, the Nordic countries have enjoyed outstanding success in distance running. In the 1910-20s, the dominance of Finnish runners was a feature of the first year-round systematic training. During the Second World War, the Swedish coach Gosta Holmer developed the fartlek (speed play) method, which enabled his runners to set numerous world records between 1500 meters and 10,000 meters. The most significant innovation in modern distance running training methods was the scientifically based interval training of the German Dr. Woldemar Gerschler, which still determines the training of athletes today. Based on empirical observations, the Dutchman Herman Verheul developed his easy interval method based on the Gerchler system. The Verheul method was characterized by high-volume and mainly aerobic sub-maximal speeds, and a big emphasis on aerobic development. This can be considered the basis of the Norwegian training method that dominates sports science research today. The latter is dominated by the use of longer intervals (1000-2000 meters) developing anaerobic speed (vLT2) monitored by lactate measurement several times a week. These innovations have been fostered by various sociological reasons (promotion of sports, sports sciences, and use of the results) and the historical context of the era.